Understanding deviance - Downes, David (Oxford University Press, 2003)
This is the new edition of the popular textbook, Understanding Deviance, which guides the new student through the major sociological theories of crime, deviance and control. It offers an in-depth discussion of all the prominent theories of deviance, examining significant frameworks of the sub-discipline; from the early work of the University of Chicago in the 1920s, through issues such as functionalism and symbolic interactionism, and brings the reader fully up to date with a thorough treatment of Left Realism and 'third way' policies under New Labour